Comparing centralized and point‐of‐use treatments of per‐ and polyfluoroalkyl substances. Issue 6 (28th December 2021) - Bixler, Taler S.; Song, Cuihong; Mo, Weiwei
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) chemicals are a growing threat to public health and safety. This study seeks to compare the life cycle environmental, economic, and human health performances of centralized and point‐of‐use (POU) systems used to upgrade existing drinking water treatment facilities for enhanced PFAS removal, using Merrimack, NH as a testbed. Out of all studied system upgrade scenarios, a POU scenario that combines granular activated carbon and ion exchange filters has the lowest environmental and human health impacts and relatively low economic impact. Despite all drinking water taps in the house being protected, the centralized scenario does not perform the best in terms of the health impacts because of its relatively low perfluorooctane sulfonate removal efficiency. This suggests a potential tradeoff between protecting the highest number of taps and achieving the highest removal efficiency at limited taps as two water treatment objectives.